Longitudinal Phenotypes and Mortality in Preserved Ratio Impaired Spirometry in the COPDGene Study - Wan, Emily S. (Am J Respir Crit Care Med, 2018)
Rationale: Increasing awareness of the prevalence and significance of Preserved Ratio Impaired Spirometry (PRISm), alternatively known as restrictive or Global Initiative for Chronic Obstructive Lung Disease (GOLD)-unclassified spirometry, has expanded the body of knowledge on cross-sectional risk factors. However, longitudinal studies of PRISm remain limited. Objectives: To examine longitudinal patterns of change in lung function, radiographic characteristics, and mortality of current and former smokers with PRISm. Methods: Current and former smokers, aged 45 to 80 years, were enrolled in COPDGene (phase 1, 2008–2011) and returned for a 5-year follow-up (phase 2, 2012–2016). Subjects completed questionnaires, spirometry, chest computed tomography scans, and 6-minute-walk tests at both study visits. Baseline characteristics, longitudinal change in lung function, and mortality were assessed by post-bronchodilator lung function categories: PRISm (FEV(1)/FVC < 0.7 and FEV(1) < 80%), GOLD0 (FEV(1)/FVC > 0.7 and FEV(1) > 80%), and GOLD1–4 (FEV(1)/FVC < 0.7). Measurements and Main Results: Although the prevalence of PRISm was consistent (12.4–12.5%) at phases 1 and 2, subjects with PRISm exhibited substantial rates of transition to and from other lung function categories. Among subjects with PRISm at phase 1, 22.2% transitioned to GOLD0 and 25.1% progressed to GOLD1–4 at phase 2. Subjects with PRISm at both phase 1 and phase 2 had reduced rates of FEV(1) decline (−27.3 ± 42.1 vs. −33.0 ± 41.7 ml/yr) and comparable proportions of normal computed tomography scans (51% vs. 52.7%) relative to subjects with stable GOLD0 spirometry. In contrast, incident PRISm exhibited accelerated rates of lung function decline. Subjects with PRISm at phase 1 had higher mortality rates relative to GOLD0 and lower rates relative to the GOLD1–4 group. Conclusions: PRISm is highly prevalent, is associated with increased mortality, and represents a transitional state for significant subgroups of subjects. Additional studies to characterize longitudinal progression in PRISm are warranted.